Evaluating the Effectiveness of Government Fund Placement in Strengthening Bank Performance: Evidence from BRI Before and After the Rp55 Trillion Liquidity Injection - Mira RAHMI; Tri Siswantini; Subur (Veteran Economics, Management, & Accounting Review, 2026)
This study examines the impact of government fund placement on the financial performance of PT Bank Rakyat Indonesia (Persero) Tbk (BRI) before and after the implementation of the government liquidity support program. A quantitative comparative approach was employed using monthly financial statement data from January 2025 to April 2026. Financial performance was measured using Return on Assets (ROA), Return on Equity (ROE), Loan to Deposit Ratio (LDR), and Operational Costs to Operating Income Ratio (BOPO). The observation period consisted of eight months before and eight months after the implementation of the policy in September 2025. Data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. The results show that the government fund placement program significantly improved ROA and LDR, indicating enhanced asset profitability and stronger banking intermediation. However, no significant differences were found in ROE and BOPO, suggesting that the effects of liquidity support had not yet been fully reflected in shareholder returns and operational efficiency during the observation period. These findings support Financial Intermediation Theory, which emphasizes the importance of liquidity in strengthening banks’ intermediary functions and improving financial performance. The study contributes to the literature by providing empirical evidence on the effectiveness of government liquidity intervention and offers practical insights for policymakers and bank management in evaluating liquidity support programs. Keywords: BOPO; BRI; Financial Performance; Government Fund Placement; LDR; Liquidity Support; ROA; ROE.